Structure and interactions of fish type III antifreeze protein in solution - Salvay, Andrés Gerardo (2010)
It has been suggested that above a critical protein concentration, fish Type III antifreeze protein (AFP III) selfassembles to form micelle-like structures that may play a key role In antifreeze activity. To understand the complex activity of AFP III, a comprehensive description of its association state and structural organization in solution is necessary. We used analytical ultracentrifugation, analytical size-exclusion chromatography, and dynamic light scattering to characterize the interactions and homogeneity of AFP III in solution. Small-angle neutron scattering was used to determine the low-resolution structure in solution. Our results clearly show that at concentrations up to 20 mg mL-1 and at temperatures of 20°C, 6°C, and 4°C, AFP III is monomeric in solution and adopts a structure compatible with that determined by crystallography. Surface tension measurements show a propensity of AFP III to localize at the air/water interface, but this surface activity is not correlated with any aggregation in the bulk. These results support the hypothesis that each AFP III molecule acts independently of the others, and that specific intermolecular interactions between monomers are not required for binding to ice. The lack of attractive interactions between monomers may be functionally important, allowing for more efficient binding and covering of the ice surface.